Cerebral oximetry probes-associated skin burns in pediatric patients - (:unkn) unknown (My University, 2014)
Cerebral oxygen monitoring continuously monitors cerebral oxygenation with a noninvasive technique based on near-infrared spectroscopy. In this report, we describe 2 children in whom skin burns followed the reuse of probes monitoring cerebral oxygenation with In Vivo Optical Spectroscopy.